Implementasi Jarimatika dalam Pendidikan Dasar: Pandangan Kebijakan dan Manajemen Sekolah - Defi, Wahyu Fitrina; Utama, Yudi Nanda (Tarunateach: Journal of Elementary School, 2025)
This study aims to analyze the implementation of the Jarimatika method in elementary mathematics learning from the perspective of school policy and management. Jarimatika, as a finger-based learning innovation, is believed to enhance students’ basic arithmetic skills and create an engaging and contextual learning atmosphere. However, its successful implementation depends not only on teachers’ competence but also on supportive school policies and effective management strategies applied by school leaders and educators. This research employs a qualitative approach using a case study method conducted in several elementary schools that have implemented Jarimatika. Data were collected through interviews, observations, and analysis of school policy documents. The findings indicate that the effectiveness of Jarimatika implementation is significantly influenced by internal policies that support learning innovation, continuous teacher training, and the leadership role of principals in fostering an open and change-oriented school climate. Furthermore, adaptive and participatory school management has been proven to facilitate the integration of Jarimatika into the curriculum and daily learning activities. These findings emphasize the importance of synergy between school policy and managerial practice in improving the quality of mathematics learning in elementary education.